2014
DOI: 10.5966/sctm.2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Neural Precursor Cell Transplantation Enhances Functional Recovery and Reduces Astrogliosis in Bilateral Compressive/Contusive Cervical Spinal Cord Injury

Abstract: Spinal cord injury has a significant societal and personal impact. Although the majority of injuries involve the cervical spinal cord, few studies of cell transplantation have used clinically relevant models of cervical spinal cord injury, limiting translation into clinical trials. Given this knowledge gap, we sought to examine the effects of neural stem/precursor cell (NPC) transplants in a rodent model of bilateral cervical contusion-compression spinal cord injury. Bilateral C6-level clip contusion-compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 68 publications
(124 reference statements)
6
39
0
Order By: Relevance
“…Given the complex functional role of reactive astrocytes, it is unclear whether the finding of glial scar reduction after ep-iPSC-NPC transplantation was beneficial or detrimental for functional recovery in this study. Previous studies have reported that transplanted NPCs reduce glial scar formation and functional recovery as found in our study [11,43,[58][59][60]. One possible explanation is that a reduction in glial scarring is attributable to the indirect effect of transplanted ep-iPSC-NPCs by the amelioration of inflammation.…”
Section: Stem Cells Internationalsupporting
confidence: 75%
“…Given the complex functional role of reactive astrocytes, it is unclear whether the finding of glial scar reduction after ep-iPSC-NPC transplantation was beneficial or detrimental for functional recovery in this study. Previous studies have reported that transplanted NPCs reduce glial scar formation and functional recovery as found in our study [11,43,[58][59][60]. One possible explanation is that a reduction in glial scarring is attributable to the indirect effect of transplanted ep-iPSC-NPCs by the amelioration of inflammation.…”
Section: Stem Cells Internationalsupporting
confidence: 75%
“…Stem cell transplantation represents a promising therapeutic approach to treat neuroinflammatory and neurodegenerative disorders. By using experimental murine models of neuroinflammatoy diseases, such as experimental autoimmune encephalomyelitis (EAE), traumatic brain injury (TBI) and spinal cord injury (SCI), several studies demonstrated that stem cells reduce neurological deterioration and protect the central nervous system (CNS) from further damage and even stimulate its repair [ 1 7 ]. In these studies both adult-derived bone marrow mesenchymal stem cells (MSCs) and newborn CNS-derived neural stem cells (NSCs) provided neurotrophic support and even replaced damaged oligodendrocytes and neurons [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immuno-electron microscopy (EM) remains the best method to verify remyelination of host axons with engrafted cells. Only 20% of these studies provided evidence of exogenous remyelination via immune-EM, although five studies used confocal microscopy to identify close apposition of oligodendrocyte marker-expressing, fluorescent protein expressing-engrafted cells to host neurofilament-expressing axons (Hawryluk et al, 2014; Hu et al, 2013; Karimi-Abdolrezaee et al, 2010; Plemel et al, 2011; Wilcox et al, 2014). The ability of grafted cells to simply differentiate into oligodendrocytes with the potential to remyelinate was investigated using immunohistochemical staining against markers for mature oligodendrocytes (i.e.…”
Section: Resultsmentioning
confidence: 99%